2003
DOI: 10.1038/nrc1016
|View full text |Cite
|
Sign up to set email alerts
|

Cancer selection

Abstract: Cancers are often thought to be selectively neutral. This is because most of the individuals that they kill are post-reproductive. Some cancers, however, kill the young and so select for anticancer adaptations that reduce the chance of death. These adaptations could reduce the somatic mutation rate or the selective value of a mutant clone of cells, or increase the number of stages required for neoplasia. New theory predicts that cancer selection--selection to prevent or postpone deaths due to cancer--should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
186
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(194 citation statements)
references
References 55 publications
4
186
0
4
Order By: Relevance
“…Evolution of genes and genetic systems promoting cancer Recent studies have shown how genes promoting cancer can spread via the pleiotropic effects of strong selection in other contexts [40,41]. Thus, pediatric cancers are rare, apparently as a result of their strongly negative fitness effects, but they are concentrated in two tissues, brain and bone, that have undergone striking recent evolutionary increases in size and growth trajectories along the human lineage.…”
Section: Evolution Of Cancer Risk and Anticancer Adaptationmentioning
confidence: 99%
See 3 more Smart Citations
“…Evolution of genes and genetic systems promoting cancer Recent studies have shown how genes promoting cancer can spread via the pleiotropic effects of strong selection in other contexts [40,41]. Thus, pediatric cancers are rare, apparently as a result of their strongly negative fitness effects, but they are concentrated in two tissues, brain and bone, that have undergone striking recent evolutionary increases in size and growth trajectories along the human lineage.…”
Section: Evolution Of Cancer Risk and Anticancer Adaptationmentioning
confidence: 99%
“…Such effects might have arisen as a byproduct of rapid shifts in the rate and timing of cell proliferation systems [42,43]. Similarly, a third tissue with high pediatric cancer rates, white blood cells, is subject to the effects of strong selection from host-parasite coevolution [41].…”
Section: Evolution Of Cancer Risk and Anticancer Adaptationmentioning
confidence: 99%
See 2 more Smart Citations
“…Another explanation is the genetic instability of tumor cells leading to continual mutational progression with the consequent considerable phenotypic and genotypic evolution. [13] In conclusion, while the tumor heterogeneity hypothesis can explain the discordant KRAS mutation in the lung mucinous adenocarcinoma compared to the previous rectal mucinous adenocarcinoma and hence support a diagnosis of metastasis, the low frequency of intratumoral heterogeneity, the convincing CK20 negativity, and overall lepidic pattern seen in the mucinous adenocarcinoma found in the lung, led us to favor a lung primary over a metastasis from the rectal mucinous adenocarcinoma. In rare circumstances of two tumors showing the same morphology, sometimes checking for gene mutations, and even specific mutation sequence can help differentiate between two different primaries versus a metastasis.…”
Section: Discussionmentioning
confidence: 99%